1998
DOI: 10.1038/sj.hdy.6884250
|View full text |Cite
|
Sign up to set email alerts
|

Fitness of backcross and F2 hybrids between weedy Brassica rapa and oilseed rape(B. napus)

Abstract: With the cultivation of genetically modified crops, transgenes may spread by introgression from crops into weedy and wild populations of related species. The likelihood of this depends in part on the fitness of first and later generation hybrids. We here present results on the fitness of F 2 and backcross hybrids between oilseed rape (Brassica napus) and weedy B. rapa. Two populations of B. rapa, two varieties of B. napus, and their F 1 hybrids were used for controlled crosses, and seed development, survival i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 7 publications
4
62
0
Order By: Relevance
“…No data were available for the survival of Br( )×F 1 zygotes in pods of mixed parentage, only data from single donor crosses in Hauser et al (1998a, b). To account for the effect of competition and preferential abortion, we calculated a 'competition factor' by scaling the survival of F 1 zygotes (relative to B. rapa) within mixed pods (0.48; Hauser et al, 1997) to their relative survival in single-donor pods (0.74; Hauser et al, 1998a; 'competition factor' = 0.65). The survival of backcross zygotes in mixed pods was then estimated by multiplying their survival in pure pods ((relative to B. rapa) = 0.62; Hauser et al, 1998b) with the competition factor: u 3·· = 0.62 × 0.65 = 0.40.…”
Section: Discussionmentioning
confidence: 99%
“…No data were available for the survival of Br( )×F 1 zygotes in pods of mixed parentage, only data from single donor crosses in Hauser et al (1998a, b). To account for the effect of competition and preferential abortion, we calculated a 'competition factor' by scaling the survival of F 1 zygotes (relative to B. rapa) within mixed pods (0.48; Hauser et al, 1997) to their relative survival in single-donor pods (0.74; Hauser et al, 1998a; 'competition factor' = 0.65). The survival of backcross zygotes in mixed pods was then estimated by multiplying their survival in pure pods ((relative to B. rapa) = 0.62; Hauser et al, 1998b) with the competition factor: u 3·· = 0.62 × 0.65 = 0.40.…”
Section: Discussionmentioning
confidence: 99%
“…In similar studies, Hauser et al (1998a) found that F 1 hybrids had intermediate fitness between the two parental species based on several combined characteristics, and they concluded that F 1 hybrids were significantly more fit than weedy B. rapa. In a subsequent study, Hauser et al (1998b), found that a fitness penalty occurred in F 2 and backcrossed individuals, although a small percentage of hybrids were as fit as the weedy parent. The fitness of F 1 hybrids may also be frequency dependent (based on hybrid versus parent ratio), and the experimental design in future research may need to include the appropriate ratio of hybrid to parental weedy B. rapa plants to simulate selection for the hybrids with the highest fitness (Pertl et al 2002;Hauser et al 2003).…”
Section: Female Parent)male Parent Citationmentioning
confidence: 99%
“…Mixing the parental genomes, especially by recombination in F 2 and later generation hybrids, may break up local adaptations and intrinsic coadaptations of gene complexes (Lynch, 1991), an effect called outbreeding depression. In the case of hybridization between polyploid cultivars and diploid relatives, chromosomal imbalances may add to a low fitness of hybrids (Hauser et al, 1998a). However, hybrids between cultivated and wild plants may sometimes exhibit improved fitness relative to their parents (Ellstrand, 2003), due to inheritance of beneficial crop alleles (Campbell et al, 2006), heterosis (Hauser et al, 1998b), and novel combinations of genes and traits of the parents (Hauser et al, 1998a;Hooftman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of hybridization between polyploid cultivars and diploid relatives, chromosomal imbalances may add to a low fitness of hybrids (Hauser et al, 1998a). However, hybrids between cultivated and wild plants may sometimes exhibit improved fitness relative to their parents (Ellstrand, 2003), due to inheritance of beneficial crop alleles (Campbell et al, 2006), heterosis (Hauser et al, 1998b), and novel combinations of genes and traits of the parents (Hauser et al, 1998a;Hooftman et al, 2005). Transgression of traits from the two parents is thought to be a major mechanism for creating evolutionary novelties in hybrids (Lexer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%